Biosorption and Characterization of Metal Tolerant Bacteria Isolated from Palar River Basin Vellore (Journal of Scientific Research, 2013)
Metal pollution is a growing problem and microbes have adapted to tolerate the presence of metals and even use them. The investigation was carried out to screen for bisorption property of metals by bacteria and check for correlation between tolerance to heavy metals and antibiotic resistance. Soil samples were collected from Palar River basin site of Vellore and five distinct bacteria were isolated. Antibiotic resistance (bacitracin, chloramphenicol, streptomycin, rifampicin, penicillin and ampicillin) was checked and tolerance to heavy metals was screened (Cd, Pb, Cu and Zn). It was found that most of the bacterial isolates had multiple antibiotic resistances which might be due to the stress caused by heavy metals released into the Palar river basin, Vellore. The multiple antibiotics resistance of this bacterial species was found to be associated with tolerance to metals. Biosorption studies revealed that Alcaligenes faecalis could tolerate 59% Cd, 61% Pb, 40% Cu, 39% Zn and Staphylococcus aureus removed 60% Cd, 63% Pb, 42% Cu, 41% Zn and Streptococcus lactis absorbed 61% Cd, 57% Pb, 37% Cu, 38% Zn and Micrococcus luteus reduced 56% Cd, 61% Pb, 39% Cu, 41% Zn and Enterobacter aerogenes removed 60% Cd, 55% Pb, 62% Cu, 67% Zn. Keywords: Antibiotic resistant; Heavy metal tolerance; Biosorption; Metal polluted soils. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.14678 J. Sci. Res. 6 (1), 125-131 (2014)